Uji Daya Hambat Formula Gel Ekstrak Etanol Daun Murbei (Morus alba L.) Sebagai Anti Acne Terhadap Bakteri Propionibacterium acne.: Inhibition Test of Ethanol Extract Gel of Mulberry (Morus alba L.) Leaves as an Anti Acne on Propionibacterium acne Bacteria - Aliah, Ahmad Irsyad; Wahyuni, Wahyuni; Bachri, Nurjannah (Universitas Tadulako, 2019)
A research on the inhibition of formula gel test ethanol extract of leaves of mulberry (Morus alba L.) as an anti-acne against bacteria Propionibacterium acne. This study uses a gel formulation made using mulberry leaf extract (Morus alba L.), which aims to determine the inhibition of antibacterial gel mulberry leaf extract (Morus alba L.) against the bacteria Propionibacterium acne. Gel made three dosage concentrations of 2%, 4% and 6%. Testing inhibition of antibacterial gel agar diffusion method. Test Antibacterial inhibition obtained by looking at the clear zone in the medium and measured using calipers. The results showed that the inhibition of antibacterial gel formulation with a concentration of 2%, 4% and 6% showing that inhibiting bacterial activity.